Mary Ingalls on her own - Kimmel, Elizabeth Cody (Little house., 2008)
In 1881, sixteen-year-old Mary Ingalls becomes a student at the Iowa College for the Blind, where she studies academic subjects and learns skills that will allow her to be independent and to earn a living.